Security evaluation on Simeck against zero‐correlation linear cryptanalysis. (1st January 2018) - Zhang, Kai; Guan, Jie; Hu, Bin; Lin, Dongdai
Abstract : Since proposed by the National Security Agency in June 2013, two lightweight block ciphers‐SIMON and SPECK have attracted the attention of cryptographers from all over the world. At CHES 2015, Simeck, a new block cipher inspired from both SIMON and SPECK is proposed, which is more compact and efficient. However, the security evaluation on Simeck against zero‐correlation linear cryptanalysis seems missing from the specification. The main focus of this study is to fill this gap and evaluate the security level of Simeck against zero‐correlation linear cryptanalysis. According to the authors' study, 11‐, 13‐ and 15‐round zero‐correlation linear distinguishers on Simeck32/48/64 are proposed, respectively, then zero‐correlation linear cryptanalysis on 21‐, 24‐, 28‐round Simeck32/48/64 are first proposed. As far as they know, for Simeck32, their result is the best result up to date.